Aymara Linguistics and Literature: Actual state - Briggs, Lucy T. (1987)
Aymara is a language of the Jaqi (Hardman) or Aru (Torero) family, spoken by some three million inhabitants of the Andean highlands, from the shores of Lake Titicaca and some valleys to the east and west of the Andean mountain range, to the north of Chile and Argentina. The other members of the family are Jaqary and Kawki, spoken in Yauyos, Lima, Peru (Hardman 1983). The majority of Aymara speakers are found in Bolivia (La Paz, Oruro, North and West Potosí), where they make up almost a third of the national population.